Prospects and challenges of fish for food security in Africa - Chan, Chin Yee; Tran, Nhuong; Pethiyagoda, Shanali; Crissman, Charles C.; Sulser, Timothy B.; Phillips, Michael J. (Elsevier, 2019)
Fish contribute to Africa's food and nutrition security, but future directions for the fish sector remain uncertain. Using a structural foresight modeling approach, this paper examines past, present, and future trends of fish supply and demand in Africa to highlight challenges and prospects of the fish sector's contribution to food security in the continent. If historical trends are maintained, growth of aquaculture and fisheries would be slow, resulting in declining per capita fish consumption. Alternative scenarios highlight the potential importance of African aquaculture development in addressing food security. Policies to promote sustainable aquaculture, reduce post-harvest losses, and facilitate fish trade are indispensable. Fish deserves more attention in food and nutrition policies due to its prominence in the African food basket.